Peran Akuntansi Syariah Perspektif Muamalah dalam Mendorong Pertumbuhan Ekonomi Berkelanjutan - Muammar Khaddafi; Ahmad Fauzi Sarumpaet; Nabila Luthfi; Nita Khairani; Khairun Nisa; Muhammad Eggy Atamy (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the role of Islamic accounting in the muamalah perspective as an important instrument in promoting sustainable economic growth. Islamic accounting, which is based on the principles of fairness, transparency, and benefit, plays a role not only in recording financial transactions, but also in ensuring business practices are in accordance with Islamic law. In the context of muamalah, principles such as the prohibition of riba, gharar, and maisir encourage the creation of a fair and stable economic system. This research uses the literature review method by analyzing relevant theories and previous research. The results of the study show that the implementation of Islamic accounting not only provides benefits for business people, but also contributes to sustainable development goals, such as poverty reduction, social welfare improvement, and environmental preservation. Thus, the application of Islamic accounting in muamalah practice can be a holistic solution to realize sustainable and equitable economic growth.